AMORPHOLISM OF SILICON CRYSTAL WHEN IMPLANTED WITH LIGHT IONS - Arzikulov E.U; Sharafova T. S; Norjigitova M. (Galaxy International Interdisciplinary Research Journal, 2021)
At present, the accumulation of structural defects and the processes of transition of crystalline silicon to the amorphous state are well studied in [1, 2]. It is established by various physical methods that when ions are implanted in silicon, a large number of vacancy clusters are formed and when fully amorphous, their concentration reaches 3.21020 см-3. Various mechanisms have been used to explain this effect: diffusion-coagulation in [3], the result of the accumulation of defects up to the limit concentration in [4], etc. In most of the proposed mechanisms,amorphization is mainly associated with point defects. However, due to the high mobility of the interstitial atoms, the burning of vacancies is more pronounced than the formation of vacancy type clusters with a concentration of 1020 см-3.